Peningkatan Kualitas Air Bersih di Desa Rancatungku Melalui Sistem Filter Berbasis Metode Backwash - Aldy Fadilah; Usamah Rizqi Alfian; Fikri Triandi Thabrani; Kharisman Kharisman; Dipa Nur Madyan; Karina Marwahati; Fery Herliana; Filly Pravitasari (Universitas Insan Cendekia Mandiri, 2026)
The availability of clean water is a basic necessity for communities, playing a crucial role in supporting health, sanitation, and quality of life. However, in many rural areas, the quality of available water still does not meet proper standards due to limited access to simple and sustainable water treatment technologies. Rancatungku Village, located in Pameungpeuk District, Bandung Regency, is one of the areas facing clean water quality issues such as turbidity, yellowish color, and unpleasant odor, despite having government-provided clean water facilities. This condition affects the comfort and health of the community in fulfilling daily domestic needs. This community service activity aims to design, build, and implement a clean water filtration system based on the backwash method as an appropriate technology that is economical, effective, and easy to maintain by the community. The implementation methods include field observation, community needs analysis, designing a dual-tank filtration system with a combination of silica sand, zeolite, manganese greensand, and activated carbon media, equipment installation, operational trials, as well as socialization and maintenance training for residents. A participatory approach was applied by directly involving the community in each stage of the activity. The results of implementation show that the backwash-based water filtration system significantly improves water quality based on visual parameters, namely reduced turbidity, elimination of yellowish color, and decreased unpleasant odor. The backwash mechanism simplifies the cleaning process of filter media without dismantling, thereby increasing operational efficiency and system lifespan. Active community participation in installation and training also supports program sustainability. Thus, the backwash-based water filtration system has the potential to serve as an appropriate technology solution that can be replicated to address clean water problems in rural areas.